The Effectiveness of the Fifteen Minute Qur'anic Literacy Program (LIMIT) in Madrasah Ibtidaiyah: An Analysis of Effects, Mechanisms, and Implementation Fidelity - Zahra, Zahra; Usman, Nasir; Niswanto, Niswanto (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study investigates the effectiveness and mechanisms of the Fifteen-Minute Qur’anic Literacy Program (LIMIT) implemented in elementary madrasahs of Krueng Sabee District, Aceh Jaya, Indonesia. Designed to address low Qur’anic reading proficiency among young learners, the study employed a mixed-methods approach combining quantitative pre–post testing (n = 90; 30 per school) and qualitative interviews, observations, and document analyses. Results revealed significant improvements across all literacy components—tartīl, tajwīd, makharij, and adab—with p < .001 and a large effect size (Cohen’s d = 2.4). The fidelity index reached 86.7%, with time-on-task consistency (94%) and parent involvement (78%). Qualitative mapping identified five core drivers of success: 15-minute micro-timing, certified teacher-models, peer-tutoring loops, parental reinforcement, and data-driven monitoring. LIMIT proved to be a low-cost, high-impact intervention, requiring only Rp 3,200 per student annually, and demonstrated high social acceptance (M = 4.6/5). The findings contribute an integrative micro-intervention framework for Qur’anic literacy that is effective, efficient, and replicable within Islamic elementary education